PELATIHAN KEWIRAUSAHAAN BAGI MUSLIMAH SAGULUNG - Dian Lestari siregar; Jontro simanjuntak (LPPM-Universitas Batam, 2023)
The Muslimah Saroll group is a home-based business group that has a lot of sagulung in the city of Batam. The problems faced by the Muslimah Saroll group are low sales levels, as well as weaknesses in the product marketing aspect, especially in the sales distribution channels for their products. This PKM activity aims to increase entrepreneurial expertise and skills. The results of PKM activities for the Saroll Muslim Women Group are in the form of increasing the productivity of the Saroll Muslim Women Group from entrepreneurship training assistance as well as increasing expertise and skills in marketing handicraft products.